2006
DOI: 10.1016/j.ydbio.2006.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Minor proteins and enzymes of the Drosophila eggshell matrix

Abstract: The Drosophila eggshell provides an in vivo model system for extracellular matrix assembly, in which programmed gene expression, cell migrations, extracellular protein trafficking, proteolytic processing, and cross-linking are all required to generate a multi-layered and regionally complex architecture. While abundant structural components of the eggshell are known and are being characterized, less is known about non-abundant structural, regulatory, and enzymatic components that are likely to play critical rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 60 publications
(75 reference statements)
2
66
0
Order By: Relevance
“…The transcript of the VM26A.2 gene, encoding the most abundant component of the vitelline membrane, is detected in all follicle cells surrounding the oocyte from stage 8. The same expression pattern was observed for the VM26A.1 gene and for the CG9050 gene (Burke et al, 1987;Popodi et al, 1988, Fakhouri et al, 2006. Conversely, the VM32E gene shows a peculiar spatial transcriptional profile and its expression is restricted at stage 10 of oogenesis (Gargiulo et al, 1991).…”
Section: Spatial Expression Of Eggshell Genessupporting
confidence: 64%
See 2 more Smart Citations
“…The transcript of the VM26A.2 gene, encoding the most abundant component of the vitelline membrane, is detected in all follicle cells surrounding the oocyte from stage 8. The same expression pattern was observed for the VM26A.1 gene and for the CG9050 gene (Burke et al, 1987;Popodi et al, 1988, Fakhouri et al, 2006. Conversely, the VM32E gene shows a peculiar spatial transcriptional profile and its expression is restricted at stage 10 of oogenesis (Gargiulo et al, 1991).…”
Section: Spatial Expression Of Eggshell Genessupporting
confidence: 64%
“…Among these, the Femcoat protein is specifically expressed in the follicle cells at late stages and it is required for endochorion formation (Kim et al, 2002). In a recent effort to find unknown proteins playing relevant structural or regulatory roles in eggshell biogenesis, 11 new distinct proteins have been identified as structural components of the eggshell (Fakhouri et al, 2006). Among these three are putative vitelline membrane proteins, seven are putative chorion components and one is a novel protein.…”
Section: Timing Of Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…6) and is no longer detectable by the end of the last larval stage. The lack of any shape alteration in TwdlD 1 embryos (data not shown) presumably reflects the fact that the surrounding eggshell is a protein-based extracellular matrix distinct from cuticle (30). Within the eggshell, however, the embryonic cuticle structure is clearly affected, as is evident upon examination of newly hatched first-instar larvae (see Fig.…”
Section: Role Of Tweedle Proteins In Cuticle Assemblymentioning
confidence: 83%
“…Of note, our experiments also showed variable patterns of vitelline membrane proteins, as determined by confocal microscopy. Thus, for example, the locations of Nasrat and VM32E, which have been assigned to the vitelline membrane by electron microscopy (Andrenacci et al, 2001) and identified as eggshell proteins by proteomics (Fakhouri et al, 2006), often do not overlap when viewed by confocal microscopy (Jiménez et al, 2002). This observation might indicate heterogeneity within the vitelline membrane or differences in antibody accessibility or recognition caused by sample processing and/or distinct fixation procedures used for confocal microscopy or for electron microscopy.…”
Section: Resultsmentioning
confidence: 99%